Analysis of the efficiency of external cooling of low-speed, long-stroke, non-lubricated reciprocating compressor stages - S. S. Busarov; D. I. Bukhanets; D. C. Titov (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The theoretical analysis of the working processes of the slow-moving long-range stage with variant cooling of different sections of the working chamber made it possible to determine the rational range of its cooled zones and the corresponding design parameters of the cooling jacket, which makes it possible to ensure the permissible temperature of the injected gas at minimum overall dimensions and mass